FEMINIMISME DALAM KONSTELASI POLITIK LOKAL DI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BUNGO PERIODE TAHUN 2019-2024 - Maryam, Siti; Miranti, Miranti; Setyoko, Joko (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
In today's modern politics, the presence of women in the world of politics is urgent. Democracy also mandates equal access and participation of women and men on the basis of equality, in all areas and levels of public life, especially in decision-making positions. Currently, the issue of gender equality has become a prominent issue in development platforms, not only in Indonesia but also in the world. Looking back, in the past, women's position in politics was marginalized, women had a very small portion compared to men. This is because there is a patriarchal culture that is not friendly towards women. The constructive socio-cultural understanding that was adopted at that time placed women as if they were only allowed to take care of domestic matters. In Bungo Regency, the results of the 2019 legislative election produced 5 DPRD members who were women. It is hoped that their existence will be able to fight for women's needs. This research was conducted on the performance of Council members in accommodating and conveying to the government the needs of women. women's rights, violence against women, reproductive health, gender equality, and promoting pro-women policies in the DPRD. The informants in this research are female members of the Council, and stakeholders. The results of this research show that the female DPRD members of Bungo Regency are trying in a limited number to take various steps to convey the aspirations of Bungo women. This can be seen from Regional Regulation Number 1 of 2021 concerning Maternal and Child Health. Then in the field there are discussion forums about femininity, for example counseling, mentoring women, etc. Apart from that, in Bungo itself, in the everyday world, such as the world of work, the world of education and the world of politics, there is no discrimination.